Effects of Deposition Time on Structural and Morphological Properties of Synthesized ZnO Nanoflowers Without Using Complexing Agent - Temel, Sinan; Gokmen, Fatma Ozge; Yaman, Elif (European Scientific Journal, ESJ, 2017)
ZnO nanoflowers have been synthesized by chemical bath deposition technique at different deposition times without using complexing agent, so it is an environmentalist study. Effects of deposition time on structural and morphological properties of ZnO nanoflowers have been investigated by Xray diffraction (XRD) method and Field Emission Scanning Electron Microscope (FESEM). XRD patterns showed that the samples had hexagonal wurtzite structure and polycrystalline nature. Grain sizes, dislocation densities and lattice parameters of the samples have been calculated. According to these results, it has been determined that the ZnO nanoflowers synthesized in very short time like 30 minutes without using complexing agent, showed the best crystallization. When the images of ZnO nanoflowers have been examined, it has seen that the structure is formed continuously and independently from each other by nanorods. It has also seen that these nanorods combine to form a flower-like structure.